Regulatory elements in the upstream region of metallothionein gene in tilapia species - Alam, Mohammad Shamimul; Jahan, Israt; Rahman, Sadniman; Jahan, Hawa; Fatema, Kaniz (Dhaka University Journal of Biological Sciences, 2021)
Tilapia is a hardy fish which can survive in water bodies polluted with heavy metals. Metal resistance is conferred by higher expression of metallothionein gene (mt) in many organisms. Level, time and tissue-specificity of gene expression is regulated through transcription factor binding sites (TFBS) which may be present in the upstream, downstream, or even in the introns of a gene. So, as a candidate regulatory region, the 5’upstream sequence of mt gene in three tilapia species, Oreochromis aureus, O. niloticus and O. mossambicus was studied. The targeted region was PCR-amplified and then sequenced using a pair of custom-designed primer. A total of only 2.7% variation was found in the sequenced genomic region among the three species. Metal-related TFBS were predicted from these sequences. A total of twenty eight TFBS were found in O. aureus and twenty nine in O. mossambicus and O. niloticus. The number of metalrelated TFBS predicted in the targeted sequence was significantly higher compared to that found in randomly selected other genomic regions of same size from O. niloticus genome. Thus, the results suggest the presence of putative regulatory elements in the targeted upstream region which might have important role in the regulation of mt gene function. Dhaka Univ. J. Biol. Sci. 30(1): 95-103, 2021 (January)